LEGAL REVIEW OF MARRIAGE LEGALIZATION (ISTBAT NIKAH) BASED ON INTEGRATED HEARING IN RELIGIOUS COURTS ACCORDING TO STUDY AT PANDAN RELIGIOUS COURT - Rivi Hamdani Lubis; Mhd. Azhali Siregar; Henry Aspan (International Journal of Synergy in Law, Criminal, and Justice, 2025)
Marriage validation or itsbat nikah through an integrated trial at the Pandan Religious Court is a legal step that aims to provide legal certainty for couples whose marriages are not registered at the Office of Religious Affairs (KUA). Based on Law Number 1 of 1974 concerning Marriage, every marriage must be registered to obtain legal recognition. However, there are still many people who carry out underhand marriages (siri) without official registration, which causes various administrative problems, such as difficulties in processing children's birth certificates, family cards, and inheritance rights. This study aims to analyze the implementation of marriage confirmation through an integrated trial at the Pandan Religious Court and its compliance with applicable laws and regulations. The method used is a normative legal approach with an analysis of related legal regulations and court decisions in marriage confirmation cases. The results of the study indicate that integrated trials provide convenience for couples who do not yet have a marriage certificate, especially for the underprivileged. However, there are challenges in its implementation, such as limited resources and low public understanding of the importance of marriage registration. With an integrated trial, marriage confirmation can accelerate the process of marriage validation and provide legal protection for couples and their children. Therefore, efforts are needed to socialize and improve regulations so that marriage confirmation can be more effective in guaranteeing the legal rights of married couples and increasing legal certainty in marriage.